Motorcycle crash detection system / Muhamad Arif Rusdin and Kamarul Arsyad Kamarudin - Rusdin, Muhamad Arif; Kamarudin, Kamarul Arsyad (2019)
A motorcycle crash detection system is presented using Arduino,SIM808 module and and accelerometer.Today motorcycle’s accidents always happen and the lack of treatment in proper time is the one of the reasons for half of deaths in road accidents.In this research,motorcycle crash detection system is created to detect the positon of the motorcyclist who involved in an accidents.This project objectives is to created a microcontroller that has the ability to detect the victim of the motorcyle accident by using Global Positioning System(GPS).The significant of this project is to reduce the number of deaths among motorcyclist.Using Internet of Things(IoT),the data can be send quick because IoT use internet connection. So,surely the help for victims will come at a proper time because this system is connected to the victims family or emergency number and this system using latest technology.The recommendation for this project is to add the function of the airbag in the system to reduce the accident’s impact at the motorcycle and the rider.This research paper shows that motorcycle crash detection system is able to locate the position of the motorcyclists who involved in any accidents.SIM808 is able to locate the position of the rider which is the main factor to save the victims life in proper time.